Fabrication of redox-active polyoxometalate-based ionic crystals onto single-walled carbon nanotubes as high-performance anode materials for lithium-ion batteries. Issue 6 (24th February 2020) - Iqbal, Bushra; Jia, Xueying; Hu, Hanbin; He, Lei; Chen, Wei; Song, Yu-Fei
Abstract : Polyoxometalate-based ionic crystals were fabricated onto single-walled carbon nanotubes as anode materials for lithium-ion batteries with high specific capacity and excellent cycling stability. Abstract : Polyoxometalate (POM)-based molecular cluster batteries have attracted wide interest due to their rich redox properties. To date, no studies on POM-based ionic crystals for LIBs have been reported, although the redox-active metals can be incorporated and finely tuned in the ionic crystals. Herein, a POM-based ionic crystal (denoted as Composite 1) was prepared for the first time by the complexation of the trinuclear acetate-bridged cobalt-containing macrocation ([Co3 O(CH3 CO2 )6 (C5 H5 N)3 ] + ) with the anion [PMo12 O40 ] 3− . Further interaction of Composite 1 and single-walled carbon nanotubes (SWNTs) resulted in the formation of a novel Composite 1/SWNT nanocomposite through a facile one-pot strategy, in which the Composite 1 clusters were uniformly grown onto the surface of SWNTs. The as-prepared Composite 1/SWNT nanocomposite showed outstanding electrochemical performance as an anode material of LIBs by delivering a storage capacity of 1012 mA h g −1 at 100 mA g −1 for 100 cycles. The results may open a new pathway for exploring novel anode materials of LIBs.